ضغط ترويسة بروتوكول الانترنت في شبكات الحساسات اللاسلكيّة باستخدام العناوين الافتراضيّة - خليفه, جمال; ايوب, ميلاد (Latakia University Journal -Engineering Sciences Series, 2016)
تفرض محدودية موارد شبكات الحساسات اللاسلكية تحدياً كبيراً على نقلها لرزمIPv6 ؛ في هذا الإطار، يكتسب ضغط ترويسة IPv6، وخاصة حقلي العنونة فيها، أهمية كبيرة؛ لكونها تشغل حوالي 31% من الحجم الأقصى لحمولة الطبقة الفيزيائية في هذه الشبكات. ندرس في هذا البحث نموذج ضغط ترويسة IPv6 في شبكات الحساسات اللاسلكية المعتمدة على بروتوكول الانترنت، بناءً على الحالة الافتراضية للضغط وفق التراسل: (حساس- عقدة خارجية). ونقدم نموذج ضغط معدلاً يعتمد على التعيين المسبق لعدد محدد من عناوين مستخدمي الشبكة كعناوين افتراضية. يوفر النموذج المقترح زيادة في نسبة ضغط ترويسة IPv6 عند التراسل بين الحساسات والمستخدمين الافتراضيين، ويخفف حمل تبادل البيانات اللازمة للضغط. يتم تقييم النموذجين الأصلي والمقترح باستخدام المحاكاة البرمجية، والدراسات المخبرية التي قمنا بإجرائها في مخبر FlockLab التابع لقسم هندسة الحاسبات والشبكات في المعهد السويسري الفيدرالي للتقانة، زوريخ، سويسرا. The limited resources of wireless sensor networks impose a major challenge on their transporting of IPv6 packets. In this context, the compression of IPv6 header, and especially its two addressing fields, acquires great importance given that it occupies about 31% of the physical layer's maximum payload size in these networks. In this paper, we study IPv6 header compression scheme in IP-based wireless sensor networks, based on the default case for compression according to (sensor–external node) communications. We also introduce a modified compression scheme which relies on the pre-allocation of a specific number of network users' addresses as default addresses. For communications between sensors and the default users, the proposed scheme increases IPv6 header compression ratio, and reduces the load of data exchange required for compression. The proposed scheme and the original one are evaluated using software simulation, and the laboratory studies which we performed at FlockLab laboratory of the Computer Engineering and Networks Department in the Swiss Federal Institute of Technology, Zurich, Switzerland.